2019
DOI: 10.1016/j.nmni.2019.100605
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of multidrug-resistance in Gram-negative bacteria from the Peshawar teaching hospital, Pakistan

Abstract: Extended-spectrum β-lactamases, carbapenemases, 16S rRNA methylases conferring pan-drug aminoglycoside resistance and colistin resistance were investigated among Gram-negative bacteria recovered from clinical samples (infections) from 200 individuals hospitalized at the Khyber Teaching Hospital of Peshawar, north Pakistan, from December 2017 to March 2018. Out of 65 isolates recovered, 19% were carbapenem resistant and 16% carried a blaNDM-1 gene, confirming the widespread distribution of NDM producers in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
8
7
1
1
Order By: Relevance
“…The most common carbapenemase gene was bla NDM 83% (44/53) followed by bla OXA-48 75% (40/53), bla VIM 49% (26/53) and bla IMP 43% (23/53), while the gene bla KPC was least frequent (4/53) ( Table 5 ). Interestingly, bla NDM was the most commonly detected carbapenemase and bla OXA-48 was second, which is consistent with other reports [ 12 , 16 , 19 , 37 ]. In addition, similar to previous analyses, the two genes bla OXA-48 and bla NDM were commonly detected with a high predominance of bla OXA-48 [ 23 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most common carbapenemase gene was bla NDM 83% (44/53) followed by bla OXA-48 75% (40/53), bla VIM 49% (26/53) and bla IMP 43% (23/53), while the gene bla KPC was least frequent (4/53) ( Table 5 ). Interestingly, bla NDM was the most commonly detected carbapenemase and bla OXA-48 was second, which is consistent with other reports [ 12 , 16 , 19 , 37 ]. In addition, similar to previous analyses, the two genes bla OXA-48 and bla NDM were commonly detected with a high predominance of bla OXA-48 [ 23 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The most prevalent bacteria were Klebsiella sp., A. baumanii, followed by E. coli and P. aeruginosa, which is similar to data from recent studies conducted in other countries [4,23,26,29,38]. Comparable to previous reports [14,38], the KPC gene was the least detected among carbapenemase-producing bacteria, even in some studies none of bla KPC was detected [28,37]. A probable explanation for the low detection rate of the KPC gene among carbapenemase-producing isolates might be that these isolates contain other class A carbapenemases (other than KPC), for example GES, Sme, NMC-A and IMI.…”
Section: Plos Onesupporting
confidence: 88%
“…Even so, in a study, the coexistence of bla NDM-1 with other ESBL genes was identified [ 21 ]. In 2019, a study from Peshawar, Pakistan resembled our findings by reporting a 16% bla NDM-1 prevalence in Gram-negative bacteria [ 22 ]. Nevertheless, some other studies have reported different patterns of prevalence for bla NDM-1 in Pakistan, i.e., 41% in 2013 and 6.8% in 2018 [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 69%
“…Asocierea genelor de rezistență la carbapenem NDM, împreună cu β-lactamază cu spectru extins CTX-M-15 și 16S rRNA metilaze, a fost frecventă, explicând modelul de multidrogrezistență observat. Toate izolatele au rămas sensibile la colistin [17].…”
Section: Rezutate șI Discuțiiunclassified